Z-line alterations and gastroesophageal reflux: an endoscopic population-based prospective cohort study. (2nd September 2019) - Wallner, Bengt; Björ, Ove; Andreasson, Anna; Vieth, Michael; Schmidt, Peter T.; Hellström, Per M.; Forsberg, Anna; Talley, Nicholas J.; Agreus, Lars
Abstract: Background and study aims: Barrett's esophagus is a premalignant condition in the distal esophagus associated with esophageal adenocarcinoma. Since gastroesophageal reflux is known to be of etiological importance in both Barrett's esophagus and esophageal adenocarcinoma, we aimed to study which endoscopic alterations at the Z-line can be attributed to a previous history of reflux symptoms. Patients and methods: From 1988, a population cohort in Sweden has been prospectively studied regarding gastrointestinal symptoms, using a validated questionnaire. In 2012, the population was invited to undergo a gastroscopy and participate in the present study. In order to determine which endoscopic alterations that can be attributed to a previous history of gastroesophageal reflux, three different endoscopic definitions of columnar-lined esophagus (CLE) were used: (1) ZAP I, An irregular Z-line with a suspicion of tongue-like protrusions; (2) ZAP II/III, Distinct, obvious tongues of metaplastic columnar epithelium; (3) CLE ≥1 cm, The Prague C/M-classification with a minimum length of 1 cm. Results: A total of 165 community subjects were included in the study. Of these, 40 had CLE ≥ 1 cm, 99 had ZAP I, and 26 had ZAP II/III. ZAP II/III was associated with an over threefold risk of previous GER symptoms (OR: 3.60, CI: 1.49–8.70). No association was found between gastroesophageal reflux and ZAP I (OR: 2.06, CI: 0.85–5.00), or CLE ≥1 cm (OR: 1.64, CI: 0.77–3.49). Conclusions: In a general community, the only endoscopic alteration to the Z-line definitely linked to longstanding GER symptoms was the presence of obvious tongues of metaplastic columnar epithelium (ZAP II/III).